Tourism : - Page, Stephen J. (Thomson Learning, 2006)
Tourism: A Modern Synthesis is an accessible core textbook for tourism focusing on the development and management of tourism in an international context. A strong business and management theme pervades the book reflecting developments in the teaching and content of modern courses. The book is based around the principles of management and includes case studies emphasising this theme. It can be used as a one semester text, but its coverage of a broad range of subjects make it a useful resource throughout the three years of a degree course.